The Role of Locus of Control in Mediating the Influence of Financial Literacy, Financial Attitudes, and Lifestyle on the Personal Financial Management Behavior of Generation Z in Banda Aceh City - Nisak, Husnun; Musnadi, Said; Sakir, A. (International Journal of Scientific Research and Management (IJSRM), 2025)
This study seeks to examine how Locus of Control (LoC) acts as a mediator in the impact of financial literacy, financial attitudes, and lifestyle on personal financial management behavior among Generation Z in Banda Aceh City. Generation Z, a demographic group that significantly influences social and economic development, often struggles with managing personal finances, especially due to uncontrolled spending habits. Using a quantitative method and PLS, this research investigates the relationships between financial literacy, financial attitudes, lifestyle, and LoC within the context of personal financial management. The findings are expected to shed light on the mediating role of LoC in the connection between financial literacy, financial attitudes, lifestyle, and financial management behavior. Additionally, the study aims to emphasize the importance of financial literacy education for Generation Z and show how enhancing attitudes and adopting a responsible lifestyle can improve personal financial management in the future. Based on the results, it is advised that government bodies and educational institutions prioritize developing financial literacy programs that incorporate the fostering of positive character traits and habits related to personal financial management for Generation Z.